Early childhood male medical circumcision - Palmer, Eurica (University of the Free State, 2022)
Medical male circumcision studies concerning decision-making often focus on acceptability and feasibility among parents, with limited application of theoretical frameworks. The involvement of Black women in medical male circumcision policies and programmes has received limited attention. The research investigated infant and child male circumcision (ICMC) decision-making in South Africa and analysed the different perspectives and debates. Furthermore, the study focused on ICMC as an HIV prevention strategy. The constructs of three theoretical frameworks, including the Social Constructivism Theory, Ecological Systems Theory, and Social Norms Theory, were applied across three independent articles. In-depth interviews were conducted to collect data from parents, Black women, and a young male participant who has undergone traditional male circumcision to determine their experiences of ICMC decision-making in the Diepsloot and Diepkloof areas in Gauteng, South Africa. The data analysis was conducted using a thematic and framework analysis. The findings showed that policy positions do not reflect the social contexts, including social sanctions, the social network, and the social construction of masculinity prevalent in ICMC decision-making. The results showed that the involvement of Black women in medical male circumcision policies and programmes should be central as men dominate ICMC decisions and women are on the periphery of the decision-making process.
Thesis (Ph.D. (Development Studies))--University of the Free State, 2022
Keywords: Infant and child male circumcision; medical male circumcision; traditional male circumcision; gender; women; Social Constructivism Theory; Ecological Systems Theory; Social Norms Theory